Afterword: a fresh look at workplace learning for VET teachers. (2nd January 2020) - Smith, Erica
ABSTRACT: The expertise and professionalism of teachers is vital in vocational education and training (VET), as it is in any other education sector. As 'dual professionals', VET teachers need to keep abreast of their industry or discipline area as well as maintaining and improving their pedagogical skills and knowledge. VET workplaces (colleges and vocational schools) are important sites of learning for these matters. This paper draws together and analyses the findings from the other papers in this special issue, finding that VET workplaces contribute to teachers' learning both as a part of pedagogical qualifications (in 'teaching practice' components) and as part of continuing professional learning. The paper draws on a previous theoretical model and the findings in the papers to propose a number of categories of workplace learning: learning that is taught, sought, wrought, caught, brought, and thought. These could be applied to any occupation. Finally, the contribution of teachers' personal attributes to the extent and nature of their site-based learning is examined, using the data in the papers to develop further a previous model of VET teacher professionalism.